The Shapes of Scaled Earnings Histograms Are Not Due to Scaling and Sample Selection: Evidence from Distributions of Reported Earnings per Share - Jorgensen, Bjorn N.; Lee, Yong Gyu; Rock, Steve (Contemporary Accounting Research, 2014)
Considerable debate continues regarding the use of earnings histograms as evidence consistent with earnings management. Durstchi and Easton (2005) offer scaling and sample selection as alternative explanations for apparent discontinuities in cross-sectionally pooled histograms of earnings. We revisit the broad question of whether irregularities in reported earnings numbers can constitute evidence consistent with earnings management. We use a matched-pair design to avoid sample selection issues and study three irregularities in reported earnings per share (EPS). We first study the discontinuity pattern in the last digit (cents) of reported EPS noted by Thomas (1989) that the last digit of EPS is more likely to be zero and five and less likely to be nine for profit firms while the pattern does not appear for loss firms. Second, we consider the threshold irregularity in EPS changes noted by Degeorge, Patel, and Zeckhauser (1999), that one-cent decreases are underrepresented, relative to expectations. Third, we also revisit the rounding pattern in (unreported) third decimals of EPS noted by Das and Zhang (2003) that the one tenth of a cent is more likely between five and nine for profit firms. Our study enhances confidence in each reported irregularity's validity by identifying matched pairs of firm-years reporting EPS under two measurement regimes: one in place during the reporting period in real time, the other subsequently reported to conform to a new reporting standard. We report evidence consistent with EPS management that is not plausibly attributable to either sample selection or scaling.